DESAIN PEMBELAJARAN "MARKET DAY" UNTUK MEMFASILITASI KEMAMPUAN LITERASI FINANSIAL ANAK USIA 5-6 TAHUN SUBTEMA BERMAIN PERAN - Devi Indrianti, - (2022)
This research is motivated by the lack of learning designs that can facilitate the financial literacy abilities of children aged 5-6 years. In addition, the teacher's lack of understanding that financial literacy is important to be conveyed from an early age makes this financial literacy not conveyed properly to children. This research aims to produce a learning design that attracts children's interest in the form of a market day learning design. The research method used is DBR (Design Based Research) with Greivemeijer and Cobb (2006) models. In this study, data were collected through interviews with teachers, which were then analyzed to make a hypothetical learning trajectory. In this study, two trials were conducted with different schools. The results of this study state that the learning tools developed are appropriate both in terms of the learning implementation plan (RPP), the Student Worksheet (LKPD), the instrument for achieving product effectiveness as a comparison of learning outcomes after using the market day learning design and the product usage instrument by the teacher as This market day learning design appraiser is valid, practical and can be used to facilitate the financial literacy skills of children aged 5-6 years.